2004
DOI: 10.1152/ajprenal.00321.2003
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of PHEX expression in bone and parathyroid gland by chronic renal insufficiency and 1,25-dihydroxyvitamin D3

Abstract: Mutations in the PHEX gene are responsible for X-linked hypophosphatemia, a renal phosphate-wasting disorder associated with defective skeletal mineralization. PHEX is predominantly expressed in bones and teeth and in the parathyroid gland of patients with chronic renal failure and tertiary hyperparathyroidism. The purpose of the present study was to examine the effects of renal insufficiency and 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] on the regulation of PHEX expression in rat tibia and parathyroid gland. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…4) is similar to the decrease in endogenous PHEX gene expression in UMR-106 cells (Fig. 1) and the in vivo decrease observed in rats (22) and mice, further suggesting similar regulation in vitro and in vivo. Moreover, this observed ϳ50% decrease in PHEX expression by 1,25(OH) 2 D 3 (Figs.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…4) is similar to the decrease in endogenous PHEX gene expression in UMR-106 cells (Fig. 1) and the in vivo decrease observed in rats (22) and mice, further suggesting similar regulation in vitro and in vivo. Moreover, this observed ϳ50% decrease in PHEX expression by 1,25(OH) 2 D 3 (Figs.…”
Section: Discussionsupporting
confidence: 83%
“…1, B and C). Furthermore, this in vivo decrease in PHEX mRNA expression is in agreement with the approximate 40% decrease in PHEX mRNA and protein expression reported by Brewer et al (22) -106 cells (19, 25). Preliminary experi-ments revealed that the promoterless vector pGL3-Basic (Promega) was itself regulated by 1,25(OH) 2 D 3 in UMR-106 cells (data not shown).…”
Section: Repression Of Phex Expression and Inhibition Of Mineralizatisupporting
confidence: 91%
See 2 more Smart Citations
“…PHEX also plays a major role in renal phosphate handling but is not expressed in the kidney, suggesting the secondary involvement of a circulating systemic factor. Recent studies confirm that PHEX expression in brain and PTH glands may also play a key role in phosphate homeostasis (Blydt-Hansen et al, 1999;Brewer et al, 2003).…”
Section: (2) Phex: a Protease And Ligand?mentioning
confidence: 90%